(untitled) (Marketing Journal, 2025)
This article provides a comprehensive overview of the procurement process in an unstable environment, emphasizing the importance of adhering to standardized procedures. It outlines six key stages: supplier identification, product/service requests, procurement proposal requests, evaluation and contract awarding, order processing and contract signing, and finally, receipt and payment. Each stage is detailed with essential steps, including mark et research, supplier evaluation criteria, documentation requirements, and compliance with quality standards. The document also highlights the significance of transparency, fairness, and proper coordination among departments to ensure an efficient and ethi cal supply chain process.